Clinical and Electrophysiological Evaluation of Neonatal Seizures - Aygun, Canan; Ozyurek, Hamit; Akça, Gülfer; Akça, Ünal; Aykanat, Mustafa Alper (My University, 2023)
Neonatal seizures are the most prevalent and distinctive sign of neurologic dysfunction in early-life. In spite the recent advances in medical care and technology in newborn intensive care units (NICU), it remains an important clinical issue of diagnosis, treatment, and prognosis. This was a retrospective, observational cohort study of neonates with seizures treated in the Ondokuz Mayıs University Faculty of Medicine NICU. Demographics of the babies, risk factors and etiology of seizure, type of clinical seizure, electroencephalographic and radiological findings, and anti-seizure treatments were recorded. The incidence of neonatal seizures was 4.5% in NICU admissions. Seventy-two babies with seizures included, 69,4% were diagnosed with electroclinical seizures. The most common seizure types were clonic (35.8%) and motor automatisms (32.8%). Perinatal asphyxia/hypoxic ischemic encephalopathy (HIE) (29.2%) was the most common etiological factor, whereas hypoglycemia was the most common metabolic problem (15.3%). Eighty-one percent of seizures due to HIE were observed in the first 48 h. Hyperbilirubinemia (kern icterus), hypocalcemia, and idiopathic neonatal convulsions were observed after the first 48 h. Abnormal findings were detected in 76.4% of electroencephalographies obtained during the neonatal period. Phenobarbital was the first-line therapy in 98.6% of babies, and 83.3% of the infants were seizure-free with phenobarbital. Seizures are common in the neonatal period and may be associated with significant brain damage. Seizures appear as an important symptom of the underlying pathology and not as a disease.